Maggot Cultivation as a Solution for Household Organic Waste Processing in Aisyiyah Denai: Budidaya Maggot Sebagai Solusi Pengolahan Sampah Organik Rumah Tangga di Aisyiyah Denai - Siregar, Sasmita; Utami, Sri; Widihastuty, Widihastuty (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Waste-related environmental pollution can affect health and needs to be addressed seriously.   These days, the majority of organic waste is turned into eco-enzymes and fertilizer.   In addition, insects can be used as bioconversion agents to control organic waste in homes.   The Black Soldier Fly, or BSF fly, is the insect.   The ladies of the Aisyiyah Branch in Medan Denai, North Sumatra Province, are the partners of the Muhammadiyah Development Partnership Program (PKPM) in this project.  By using maggots as a bioconversion agent and teaching Aisyiyah mothers about the use of maggots as fish and poultry feed, the program aims to turn household trash into a product of economic value, which should raise household income.  The technique employed in this activity began with socialization followed by maggot cultivation training for mothers. Direct interviews were conducted as a way to evaluate activities for Aisyiyah mothers. The results achieved were an increase in knowledge about maggots by around 75% and 25% of Aisyiyah mothers understood maggot cultivation.